Patients’ knowledge, attitude, and practice toward stroke rehabilitation: a web-based cross-sectional study - Qian, Xiaoling; Wang, Haixia; Wang, Xiaoyan; Wu, Tingting; Han, Hongmei; Bu, Xia; Teng, Fengling (Frontiers in Public Health, 2025)
ObjectiveThe objective of this research was to comprehensively assess how well patients understand stroke rehabilitation, their perceptions of it, and their inclination to participate.MethodsThis web-based cross-sectional study was conducted between February and June 2023 at the Second Hospital of Lanzhou University, using a self-administered questionnaire.ResultsA total of 497 valid questionnaires were enrolled, including 342 (68.81%) males. The mean score of knowledge, attitude and practice was 11.79 ± 0.63 (possible range: 0–12), 36.06 ± 2.55 (possible range: 12–60), and 58.24 ± 5.08 (possible range: 14–70), respectively. The results demonstrated that knowledge has a positive and significant direct effect on attitudes (β = 0.249, p < 0.001), and attitudes had direct effects on practice (β = 0.443, p < 0.001). Knowledge had direct (β = 0.124, p = 0.002) and indirect effects (β = 0.111, p < 0.001) on practice.ConclusionStroke patients had sufficient knowledge, unfavorable attitude and positive practice toward stroke and rehabilitation training. This study showed that addressing and enhancing individuals’ attitudes could be a key strategy in promoting more positive and effective practice toward stroke and rehabilitation training among stroke patients.